Impact of Low Muscle Mass and Low Muscle Strength According to EWGSOP2 and EWGSOP1 in Community-Dwelling Older People. (11th March 2020) - Costanzo, Luisa; De Vincentis, Antonio; Di Iorio, Angelo; Bandinelli, Stefania; Ferrucci, Luigi; Antonelli Incalzi, Raffaele; Pedone, Claudio
Abstract: Background: A universal definition of sarcopenia is still lacking. Since the European criteria have been recently revised, we aimed at studying prevalence of low muscle strength (LMS) and low muscle mass (LMM), as defined according to the European Working Group of Sarcopenia in Older People (EWGSOP) 2 and 1 definitions, and their individual contribution toward mortality and incident mobility disability in a cohort of community-dwelling older people. Methods: Longitudinal analysis of 535 participants of the InCHIANTI study. LMS and LMM were defined according to the criteria indicated in the EWGSOP2 and 1. Cox and log-binomial regressions were used to examine association with mortality and 3-year mobility disability (inability to walk 400 m). Results: We observed a lower prevalence of the combination LMM/LMS according to EWGSOP2 compared to EWGSOP1 (3.2% vs 6.2%). Using the new criteria, all sarcopenia components were associated with mortality, although the hazard ratio [HR] for the group LMM/LMS was no longer significant after adjustment for confounders (LMM: HR 2.69, 95% confidence interval [CI] 1.04–6.94; LMS: HR 3.18, 95% CI 1.44–7.01; LMM/LMS: HR 2.95, 95% CI 0.86–10.16). Using EWGSOP1, LMS alone was independently associated with mortality (HR 4.43, 95% CI 1.85–10.57). None of the sarcopenia components conferred a higher risk of mobility disability. Conclusions: The EWGSOP2 algorithm leads to a reduction in the estimated prevalence of sarcopenia defined as combination of LMM/LMS. The finding that, independent of the adopted criteria, people with LMS and normal mass have a higher mortality risk compared to robust individuals, confirms that evaluation of muscle strength has a central role for prognosis evaluation.